MEMOIRS RECORDED BY BALTIC GERMAN WOMEN: AMBIVALENT LIVES AND TIMES - Maris, Saagpakk (European Scientific Journal, ESJ, 2013)
This paper examines memoirs of Baltic German women through the light of theories of postcolonial scholar Homi K. Bhabha. The article focuses on reconstruction of Baltic German identity after significant political changes in the beginning of the 20th century. The Baltic German history of that period is the story of disappointments and adjustments. The Germans had to face numerous losses, both moral and material. Under the circumstances, the preservation of self-esteem and self-identity were a key issue. The authors perceive the schizophrenic ambivalence of their position, the incompatibility of the past and the future growing ever more distinct, and they clarify their position through the text, overcoming the contradictions by writing. The textual smoothing of ambivalence helps the authors reject in their minds the uneasy sense of unhomeliness. The authors under review in this article - Natalie von Maydell and Agnes von Baranow – make use of different strategies, beginning with the declaration of superiority and evasion of painful topics up to the employment of the rhetorical devices of political propaganda.